Lantunan gendhing Jawa untuk menggugah semangat kebangsaan - Purwadi Purwadi (FBS UNY, 2022)
This article seeks to examine Javanese gendhing which is used as a means to inspire the spirit of nationalism. Love for the homeland and the nation is an obligation for all citizens. Artists create Javanese songs to increase the sense of nationalism. For traditional Javanese people, Javanese songs are an effective medium to convey noble messages. The creation of Javanese gendhing with the theme of nationality is present as a medium of education and entertainment. By studying the virtues of Javanese songs, the younger generation is expected to be able to foster the spirit of nationalism. Keyword : Javanese gendhing, nationality, traditional society